Type 2 diabetes mellitus with early phase acute inflammatory protein on serum protein electrophoresis (Journal of Pathology of Nepal, 2012)
Background: The onset of Type 2 diabetes has been associated with low grade systemic inflammation. The inflammatory status has been studied by measuring acute phase reactant proteins like hsCRP, α1- antitrypsin, α1-acid glycoprotein, ceruloplasmin, fibrinogen. Most of these acute phase reactants form α1 and α2 bands on electropherogram of serum proteins. The aim of this study was to evaluate inflammatory status in controlled and uncontrolled type 2 diabetes using cellulose acetate electrophoresis and to find the impact of glycemic status as indicated by HbA1c on inflammation process. Materials and Methods: Serum protein electrophoresis was done on serum samples of 60 cases of Diabetes [controlled and uncontrolled] using cellulose acetate paper technique. The electropherogram obtained was stained with Ponseu S and then quantitated using densitometer. Glycemic status was studied by HbA1c analysis. The density of α1and α2 bands in electropherogram were correlated with HbA1c level. Result: A significant increase in the percentage of α1 and α2 band proteins (0.765 and 0.716, p